Between the Designer and the User: Conscious Design of ICT Tools in the Context of Disability - Lulek, Anna (Inclusive Digital Technologies: Perspectives, Opportunities, and Limitations, 2025)
Knowledge about disability and accessibility is crucial in building inclusive societies, both in thehuman and infrastructural, spatial and digital dimensions. Social (mis)understanding of accessibilityand disability issues, the deep-rooted medical model of disability and the lack of a user’sperspective deepen the designer-user gap, which in turn can perpetuate and multiply stereotypesand prejudices about people with disabilities and special needs. Te presentation explores topicsrelated to the understanding of disability by designers of modern ICT tools. Trough literatureanalysis and interviews with creators of VR, AI and digital applications on disability, an attemptwas made to show the impact that disability awareness has on the designed digital reality. In conclusion,an attempt was made to indicate how proper and continuous education and inclusion ofpeople with disabilities in the design process can prevent and fll the designer-user gap.